The Effect of Organizational Commitment, Professionalism, and Ethical Behavior on Auditor Performance in Public Accounting Firms in Sumatra Region - Nazipah Putri, Wiwik; Kusumastuti, Ratih; Friyani, Rita (Asian Journal of Management Analytics, 2024)
The purpose of this study is to study how auditor performance is affected by the following factors: organizational commitment to the auditor's work, auditor professionalism, and ethical behavior. In addition, this study examines how organizational contribution, professionalism, and ethical behavior affect auditor performance. This study involved auditors from all over Sumatra who worked at Public Accounting Firms (KAP). The sample consisted of 5 regions: Jambi, Pekanbaru, Palembang, Medan, and Batam, with a total of 62 respondents. The data collection method through the SPSS 29 Software for Windows questionnaire was used to conduct the analysis of this study, which used multiple linear regression. According to the results of the study, although organizational commitment does not affect auditor performance, professionalism and ethical behavior significantly affect auditor performance. In addition, professionalism and ethical behavior affect the performance of auditors simultaneously with the organization's commitments.